2009
DOI: 10.1128/aac.00873-08
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of KsgA, a 16S rRNA Methyltransferase, Causes Vigorous Emergence of Mutants with High-Level Kasugamycin Resistance

Abstract: The methyltransferases RsmG and KsgA methylate the nucleotides G535 (RsmG) and A1518 and A1519 (KsgA) in 16S rRNA, and inactivation of the proteins by introducing mutations results in acquisition of low-level resistance to streptomycin and kasugamycin, respectively. In a Bacillus subtilis strain harboring a single rrn operon (rrnO), we found that spontaneous ksgA mutations conferring a modest level of resistance to kasugamycin occur at a high frequency of 10 ؊6 . More importantly, we also found that once cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…Previous in vitro studies showed that spontaneous KSM-resistant mutants of E. amylovora, E. coli, and Bacillus subtilis harbored mutations in the ksgA methyltransferase gene (29,33). However, our results clarified that a nucleotide substitution of the ksgA gene is not involved in KSM resistance in field isolates of B. glumae.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous in vitro studies showed that spontaneous KSM-resistant mutants of E. amylovora, E. coli, and Bacillus subtilis harbored mutations in the ksgA methyltransferase gene (29,33). However, our results clarified that a nucleotide substitution of the ksgA gene is not involved in KSM resistance in field isolates of B. glumae.…”
Section: Discussioncontrasting
confidence: 53%
“…Bacterial resistance to KSM by inactivation of the dimethyltransferase gene (ksgA) is the most frequent mechanism of spontaneous mutation in vitro (29,33). We detected nucleotide variations, but not changes in amino acids, in ksgA gene sequences between KSM-susceptible B. glumae strains 210 and 3 (see Fig.…”
Section: Antibacterial Susceptibility Of Ksm-resistant Isolatesmentioning
confidence: 77%
“…However, the importance of studying low-level resistance to antibiotics has increased in both medical and industrial microbiology. For example, we recently found that low-level resistance to streptomycin was due to a mutation in the rsmG gene, which encodes a 16S rRNA methyltransferase, and that low-level resistance to kasugamycin was due to a mutation in the speD gene, which encodes S-adenosylmethionine decarboxylase (25,26,29). These findings provided clues to study the mechanism of high-frequency appearance of highlevel streptomycin resistance in Mycobacterium tuberculosis (30) and the overproduction of antibiotics by Streptomyces coelicolor (25).…”
mentioning
confidence: 99%
“…Loss of RsmG activity confers low-level streptomycin resistance and inexplicably prompts the appearance of high-level streptomycin resistance mutations in the S12-encoding gene, rpsL (Nishimura et al 2007a,b;Okamoto et al 2007;Gregory et al 2009;Wong et al 2011). Moreover, the effects of rsmG mutations on bacterial fitness and translational accuracy have been reported as being variable, depending on the bacterial species (Nishimura et al 2007b;Okamoto et al 2007;Gregory et al 2009;Ochi et al 2009). We recently found that a null rsmG mutation produces an error-prone phenotype in certain genetic backgrounds, which suggests that modification m 7 G527 is important for ribosomal accuracy and that pleitropy may explain, at least partially, the observed variability (A Benítez-Páez, M Villarroya, and M-E Armengod, in prep.…”
Section: Introductionmentioning
confidence: 99%